Familiarisation to and reproducibility of cycling at 110% peak power output - Higgins, M. F.; James, R. S.; Price, M. J. (The Journal of Sports Medicine and Physical Fitness, 2014)
Aim: This study investigated the familiarisation to and test re-test reproducibility of constant load cycling at 110% peak power output (WPEAK). Methods: Eleven healthy, but not cycle trained, males performed a graded incremental exercise test to ascertain WPEAK followed by three trials (T1, T2 and T3) at 110% WPEAK to exhaustion. Trials were separated by ~7 days. Results: Although there was no difference in time to exhaustion (TLIM) between T1 and T2 (P=0.100) and T2 and T3 (P=0.095) respectively, a difference was observed between T1 and T3 (P=0.046). Correlation coefficients, coefficients of determination, limits of agreement (LoA) and within-subject coefficient of variation (CV) improved across trials demonstrating T2 and T3 had the strongest relationship (T1 vs. T3: r=0.73; r2=0.53; Bias=40 s; CV=14%; T1 vs. T2: r=0.66; r2=0.43; Bias=24 s; CV=10%; T2 vs. T3: r=0.97; r2=0.95; Bias=16 s; CV=7%). There was no difference across trials for HR (P=0.12), BLa (P=0.76), RER (P=0.52), VE, (P=0.32), VO2, (P=0.33), local RPE (RPEL; P=1) and overall RPE (RPEO; P=0.91) at exhaustion or BLa (P=0.76) and pH (P=0.47) 5-minutes post-exercise. Conclusion: Constant load cycling at 110% WPEAK is a reliable protocol when assessing supramaximal exercise performance after completion of two familiarisation trials.